(untitled) (Asian Journal of Pharmaceutics (AJP), 2021)
Purpose: The objectives of present study were to evaluate the properties of a behavior modification of people in India associated with coronavirus outbreak. The behavior modification is measure of coronavirus related psychopathology, which was validated through a large sample study on adults who reported significant change in behavior due to watching and reading about coronavirus pandemic. Methods: Door to door and online survey conducted in Morena and Gwalior District, Madhya Pradesh, India, for collection of data of 1050 adults’. The partakers were contacted individually, through online and complete information were taken out through a questionnaire of different parameters. Because the study focused on the effect of thinking and/or watching about coronavirus disease 2019 (COVID-19) on physical activity of body, behavior, mental stress, anxiety, faith in God, and appetite. Results: A total of 16 symptoms of behavior modification due to coronavirus outbreak were statistically defined through a principal component analysis with Varimax rotation. The results were confirmed by a two-component structure and the total variance explained 55.23% for first component accounting. The six prime loadings on the first component were selected for the behavior changes because these loadings well exceeded the criteria for psychometrically prime items. Especially, communalities extraction coefficients (CEC) ranged from 0.717 to 0.853, coefficients of structure/pattern ranged from 0.71 to 0.90, and cross-loadings ranged from 0.17 to 0.22. These symptoms were used for the determination of different parameters such as decreased physical activity, psychological disturbances, mental stress, anxiety, faith in God, and appetite before arising COVID-19 infection and were highly reliable (α = 0.83) as a cluster. Conclusion: For the coronavirus outbreak, models will be required for control the negative behavior modification of peoples so that they can use their skill for positive outcomes. The clear cut updated policy of should be implemented to reduce these types of modifications. The prime symptoms of behavior modification were validated and stabilized through statistical tools such as CEC, coefficients of structure/pattern, and analysis of variance. Hence, we can say that if opinions of some experts are correct, then world’s most of population need special care to avoid behavior modification due to coronavirus outbreak.